2014
DOI: 10.1371/journal.pone.0078494
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Conformations in Hepatitis C Virus p7 Protein Account for Proton Transport and Dye Release

Abstract: The p7 protein from the hepatitis C virus (HCV) is a 63 amino acid long polypeptide that is essential for replication, and is involved in protein trafficking and proton transport. Therefore, p7 is a possible target for antivirals. The consensus model for the channel formed by p7 protein is a hexameric or heptameric oligomer of α-helical hairpin monomers, each having two transmembrane domains, TM1 and TM2, where the N-terminal TM1 would face the lumen of this channel. A reported high-throughput functional assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…p7 channels also adopt multiple conductance states and exhibit 'burst activity', with a strong influence afforded by the membrane environment, potentially via effects on the overall channel structure. p7 from a variety of genotypes has also been shown to conduct small molecules, such as the pH-sensitive fluorophore HPTS (8-hydroxypyrene-1,3,6-trisulfonic acid) (Wozniak et al, 2010) and carboxyfluorescein (StGelais et al, 2007), indicative of channel-pore dualism; one study recently questioned the relevance of such behaviour (Gan et al, 2014), yet indirect systems are widely utilized in viroporin studies, including by these same authors , and results faithfully and consistently reproduced those obtained for infectious HCV culture (Foster et al, 2011(Foster et al, , 2014Griffin et al, 2008;Wozniak et al, 2010). In this regard, the ability of p7 to mediate proton conductance within infected Huh7 cells remains the only activity for which a biologically relevant function has been assigned within the HCV life cycle (Wozniak et al, 2010), although roles for other observed conductances cannot be ruled out.…”
Section: Hcv P7mentioning
confidence: 99%
“…p7 channels also adopt multiple conductance states and exhibit 'burst activity', with a strong influence afforded by the membrane environment, potentially via effects on the overall channel structure. p7 from a variety of genotypes has also been shown to conduct small molecules, such as the pH-sensitive fluorophore HPTS (8-hydroxypyrene-1,3,6-trisulfonic acid) (Wozniak et al, 2010) and carboxyfluorescein (StGelais et al, 2007), indicative of channel-pore dualism; one study recently questioned the relevance of such behaviour (Gan et al, 2014), yet indirect systems are widely utilized in viroporin studies, including by these same authors , and results faithfully and consistently reproduced those obtained for infectious HCV culture (Foster et al, 2011(Foster et al, , 2014Griffin et al, 2008;Wozniak et al, 2010). In this regard, the ability of p7 to mediate proton conductance within infected Huh7 cells remains the only activity for which a biologically relevant function has been assigned within the HCV life cycle (Wozniak et al, 2010), although roles for other observed conductances cannot be ruled out.…”
Section: Hcv P7mentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / b b a m e m of the lipid bilayer the same viroporin may have the potential either to establish nanometer-sized ion channels, or alternatively, participate in additional membrane permeabilization mechanisms allowing the transport of larger solutes exceeding the nanometer scale [35,36]. Interestingly, it has been observed that lipid charge influences the IC activity of some viroporins like the E protein of SARS-CoV [32], while vesicle permeabilization assays suggest that PV 2B pore-forming activity can be regulated by the negatively charged phospholipid species existing at the cytofacial monolayers of the target membranes [37].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Support for the cation permeation function of p7 comes from observations in lipid bilayers where p7 oligomerizes to form channels and conducts current (Griffin et al, 2003; Montserret et al, 2010; Pavlovic et al, 2003; Premkumar et al, 2004). In addition to assays in lipid bilayers, two-electrode voltage clamp (TEVC) of Xenopus oocytes expressing p7 (OuYang et al, 2013) and proton flux assays in liposomes (Gan et al, 2014) have reported ion conduction functionality of p7. These studies have reported that p7 conducts Na + , K + , H + and Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%